Contribution to the knowledge of lichenized mycota from Southern Brazil. I – Species of Ramboldia (Ascomycota: Lecanoraceae) - Emerson Luiz Gumboski (Acta Biológica Catarinense, 2014)
Ramboldia, a genus of lichen-forming fungi, is represented by lecideoid species with a Lecanora-type ascus and simple and persistently hyaline ascospores. Although probably common in Brazilian mycota, species of Ramboldia remains poorly recorded in the country. The collections and analyses of specimens followed the standard protocols in lichenology. Here are reported five new records to two States of Southern Brazil. Ramboldia haematites are new record to State of Santa Catarina and both, R. heterocarpa and R. russula, are new records to Santa Catarina and to State of Paraná. Descriptions, comments, figures and a key to Brazilian species are given.